2016
DOI: 10.1159/000468987
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of <b><i>Proteus mirabilis</i></b> Phage pPM_01 Isolated from Raw Sewage

Abstract: Objectives: Phage pPM_01 was previously isolated from a raw sewage treatment facility located in Batu Maung, Penang, Malaysia, and it was highly lytic against Proteus mirabilis, which causes urinary tract infections in humans. In this paper, we characterize the biology and complete genome sequence of the phage. Methods and Results: Transmission electron microscopy revealed phage pPM_01 to be a siphovirus (the first reported virus to infect P. mirabilis), with its complete genome sequence successfully determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…BLASTn searches revealed that Isf-Pm1 is closely related to Proteus phage pPM-01 (99% coverage and 96.98% sequence identity; GenBank accession no. NC_028812 ) ( 15 ). A Virus Intergenomic Distance Calculator (VIRIDIC) intergenomic distance analysis confirmed that Isf-Pm1 belongs to the pPM-01 species, which is a yet-unclassified phage of the proposed “ Pimunavirus ” genus (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…BLASTn searches revealed that Isf-Pm1 is closely related to Proteus phage pPM-01 (99% coverage and 96.98% sequence identity; GenBank accession no. NC_028812 ) ( 15 ). A Virus Intergenomic Distance Calculator (VIRIDIC) intergenomic distance analysis confirmed that Isf-Pm1 belongs to the pPM-01 species, which is a yet-unclassified phage of the proposed “ Pimunavirus ” genus (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We investigated the toxicity of the phage cocktail in Vero cells. Vero cells (2.5 × 10 4 well/plate) were plated in a 24-well plate in the presence of 100 μL of Dulbecco’s modified Eagle’s medium (DMEM; Gibco, USA) supplemented with 5% fetal calf serum (FCS; Gibco, USA) at 37°C in 5% CO 2 ( 15 ). When cells reached 70 to 80% confluence, 10 8 CFU of P. mirabilis ATCC 7002 was added to each well, followed by the addition of the phage at different MOIs (0.01, 0.1, and 1).…”
Section: Methodsmentioning
confidence: 99%
“…This cocktail was able to significantly inhibit crystalline biofilm formation in experiments simulating an established infection and completely eradicated P. mirabilis from models in experiments simulating the early stages of infection (Nzakizwanayo et al, 2016). Other P. mirabilis phages have also been characterized with therapeutic applications in mind, and include the podophages PM16, PM75 and vB_PmiP_5460 (Melo et al, 2016; Morozova et al, 2016, 2018), the Siphophage pPM_01 (Wirjon et al, 2016), and the Myophage vB_PmiP_5461 (Melo et al, 2016). Notably, phages vB_PmiP_5460 and vB_PmiP_5461 have also been demonstrated to reduce crystalline biofilm formation in models of CAUTI (Melo et al, 2016).…”
Section: Introductionmentioning
confidence: 99%